Influence of Etiology and Onset of Deformity on Spatiotemporal, Kinematic, Kinetic, and Electromyography Gait Variables in Patients with Scoliosis—A Prospective, Comparative Study. Issue 6 (15th March 2021) - Garg, Bhavuk; Gupta, Manish; Mehta, Nishank; Malhotra, Rajesh
Abstract : Scoliosis patients (adolescent idiopathic scoliosis and congenital) when compared for gait analysis showed no difference in spatiotemporal, kinematic, kinetic, and peak electromyographic activation. Alteration in gait is secondary to the existence of the deformity and does not correlate with the onset or etiology of deformity. Abstract : Study Design: Prospective comparative study. Objective: The aim of this study was to compare the spatiotemporal, kinematic, kinetic and electromyographic (EMG) gait variables in patients with adolescent idiopathic scoliosis (AIS) and congenital scoliosis and to compare these gait variables of scoliosis patients with healthy controls. Summary of Background Data: Earlier studies have solely focussed on the possibility of altered gait patterns in AIS patients; not much light has been shed on the differences in gait patterns in congenital and adolescent scoliosis patients. Methods: Forty scoliosis patients (20 each with AIS and congenital scoliosis) and 20 healthy volunteers were prospectively recruited. After thorough clinical and radiological examination, all patients underwent gait analysis in accordance with standard protocols. The outcome measures included spatiotemporal, kinetic, kinematic and EMG activity. Composite indices for gait analysis—Gait Profile Score (GPS) and Gait Deviation Index (GDI)—were also calculated. Relevant statistical tests were applied to compare the different groups. Results: No significant difference was found between the AIS and congenital scoliosis groups with respect to baseline demographic and radiological parameters. The two subgroups of scoliosis patients (AIS and congenital) did not differ significantly with respect to any of the measured gait analysis parameters. However, when compared to the healthy age-matched control group, the scoliosis patients differed significantly with respect to gait speed, stride length, step length, GDI, GPS and peak EMG activation for erector spinae, biceps femoris, semimembranosus, rectus femoris, gastrocnemious, and tibialis anterior. Conclusion: Our findings confirm the previous findings of literature regarding the alteration in gait patterns in scoliosis patients when compared to normal individuals. However, the lack of difference in gait analysis variables between AIS and congenital scoliosis patients suggests that this alteration in gait is secondary to the existence of the deformity and does not correlate with the onset or etiology of deformity. Level of Evidence : 2